2006
DOI: 10.1002/bit.20867
|View full text |Cite
|
Sign up to set email alerts
|

Malachite green‐conjugated microtubules as mobile bioprobes selective for malachite green aptamers with capturing/releasing ability

Abstract: We have developed a novel mobile bioprobe using a conjugate of a kinesin-driven microtubule (MT) and malachite green (MG) as a platform for capturing MG RNA aptamers. The fluorescence of MG increases when it is bound to an MG aptamer, allowing MT-MG conjugates to work as sensors of RNA transcripts containing the MG aptamer sequence. Kinesin motor proteins provide an effective driving force to create mobile bioprobes without any manipulation. Although the fluorescence of a small number of MG-binding aptamers is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 26 publications
1
37
0
Order By: Relevance
“…This inspired Grate and Wilson to select an RNA aptamer to bind MG and selectively target specific RNA molecules for inactivation in vivo (Grate & Wilson, 1999). An RNA aptamer to Hoechst dye 33258 was also selected to study gene regulation while RNA aptamers for Sulforhodamine B and Fluorescein were selected for potential in vivo RNA labeling (Werstuck & Green, 1998;Holeman et al, 1998). Werstuck and Green showed that they could regulate a gene in vivo which had been modified by the insertion of the Hoechst dye by adding the dye to the medium (Werstuck & Green, 1998).…”
Section: Fluorogen-binding Aptamer-based Systems With Light-up Propermentioning
confidence: 99%
See 2 more Smart Citations
“…This inspired Grate and Wilson to select an RNA aptamer to bind MG and selectively target specific RNA molecules for inactivation in vivo (Grate & Wilson, 1999). An RNA aptamer to Hoechst dye 33258 was also selected to study gene regulation while RNA aptamers for Sulforhodamine B and Fluorescein were selected for potential in vivo RNA labeling (Werstuck & Green, 1998;Holeman et al, 1998). Werstuck and Green showed that they could regulate a gene in vivo which had been modified by the insertion of the Hoechst dye by adding the dye to the medium (Werstuck & Green, 1998).…”
Section: Fluorogen-binding Aptamer-based Systems With Light-up Propermentioning
confidence: 99%
“…The nucleotides of the internal loop form a series of stacking and non-Watson-Crick basepairing interactions to create a unique binding pocket that restricts the flexibility of the dye and keeps it in a highly fluorescent state (Figure 2A, 2B). The high affinity of this aptamer for MG (K d =117 nM) and the high fluorescence enhancement that results from binding (2360-fold) have encouraged several groups to apply it to create programmable nucleic acid biosensing platforms (Babendure et al, 2003;Stojanovic & Kolpashchikov, 2004;Hirabayashi et al, 2006;Afonin et al, 2008). These will be described in more detail in the next section after we cover other efforts to develop new light-up pairs.…”
Section: Fluorogen-binding Aptamer-based Systems With Light-up Propermentioning
confidence: 99%
See 1 more Smart Citation
“…However, in achieving autonomous loading/unloading of cargoes, a new approach is required because existing systems require external stimuli such as UV-light exposure [8]- [9], ligand supplementation [10], restriction enzyme digestion or temperature fluctuation [11] to unload cargoes from gliding MTs; thus making those systems non-autonomous. This paper describes design and empirically study of a molecular transport system that autonomously loads/unloads specified cargoes using DNA strand exchange and that transports the loaded cargoes using the reverse geometry of MT motility on kinesins.…”
Section: Molecular Communication Uses Molecules (Ie Chemical Signals)mentioning
confidence: 99%
“…In the context of molecular shuttles, the release of cargo can be achieved by delivering a competitor for the cargo linkage. 23,24 Alternatives to control via activating molecules exist but are not superior. Localized heating in a cold environment 25,26 has been demonstrated; however, for kinesin motors a 10-fold difference in activation (chosen here as benchmark to define the activation zone) is difficult to achieve due to the limited range of protein stability.…”
mentioning
confidence: 99%